ASDB: database of alternatively spliced genes. - Gelfand, M S (1999)
A database of alternatively spliced genes (ASDB) has been constructed based on (i) the results of the analysis of Swiss-Prot entries containing products of these genes and (ii) clustering procedure joining proteins that could arise by alternative splicing of the same gene. ASDB incorporates information about alternatively spliced genes, their products and expression patterns. It can be searched in order to find all products of alternative splicing produced in a particular tissue or a given organism, or all variants generated by a particular transcript. ASDB currently contains about 1700 protein sequences and can be accessed via the Internet at URL http://cbcg.nersc.gov/asdb